Interventions targeting hypertension and diabetes mellitus at community and primary healthcare level in low- and middle-income countries:a scoping review - Jorge César Correia; Sarah Lachat; Grégoire Lagger; François Chappuis; Alain Golay; David Beran; On behalf of the COHESION Project (BMC, 2019)
Abstract Background Hypertension (HTN) and diabetes mellitus (DM) are highly prevalent in low- and middle-income countries (LMIC) and a leading cause of morbidity and mortality. Recent evidence on effectiveness of primary care interventions has attracted renewed calls for their implementation. This review aims to synthesize evidence pertaining to primary care interventions on these two diseases, evaluated and tested in LMICs. Methods Two reviewers conducted an electronic search of three databases (Pubmed, EMBASE and Web of Science) and screened for eligible articles. Interventions covering health promotion, prevention, treatment, or rehabilitation activities at the PHC or community level were included. Studies published in English, French, Portuguese and Spanish, from January 2007 to January 2017, were included. Key extraction variables included the 12 criteria identified by the Template for Intervention Description and Replication (TIDieR) checklist and guide. The Innovative Care for Chronic Conditions Framework (ICCCF) was used to guide analysis and reporting of results. Results 198 articles were analyzed. The strategies focused on healthcare service organization (76.5%), community level (9.7 %), creating a positive policy environment (3.6%) and strategies covering multiple domains (10.2%). Studies included related to the following topics: description or testing of interventions (n=81; 41.3%), implementation or evaluation projects (n=42; 21.4%), quality improvement initiatives (n=15; 7.7%), screening and prevention efforts (n=26; 13.2%), management of HTN or DM (n=13; 6.6%), integrated health services (n=10; 5.1%), knowledge and attitude surveys (n=5; 2.5%), cost-effective lab tests (n=2; 1%) and policy making efforts (n=2; 1%). Most studies reported interventions by non-specialists (n=86; 43.4%) and multidisciplinary teams (n=49; 25.5%). Conclusion Only 198 articles were found over a 10 year period which demonstrates the limited published research on highly prevalent diseases in LMIC. This review shows the variety and complexity of approaches that have been tested to address HTN and DM in LMICs and highlights the elements of interventions needed to be addressed in order to strengthen delivery of care. Most studies reported little information regarding implementation processes to allow replication. Given the need for multi-component complex interventions, study designs and evaluation techniques will need to be adapted by including process evaluations versus simply effectiveness or outcome evaluations.